EXCESSIVE DEBT COLLECTION BY CESSIONARIES IN ISLAMIC FINANCE DISPUTES: SUBSTANTIVE JUSTICE AND SHARIA ECONOMIC LAW ANALYSIS - Muhammad Rakhmat Alam; M. Hamidi Masykur; Nur Chanifah (CV. RADJA PUBLIKA, 2025)
The assignment of receivables (Cessie) acts as a strategic mechanism for Islamic Financial Institutions (IFIs) to manage Non-Performing Financing (NPF) and sustain liquidity. However, a significant juridical anomaly has emerged in Indonesia where the third-party assignee (Cessionary), often an unregulated individual investor, collects debts from the debtor (Cessus) at a value significantly exceeding the nominal outstanding value stated in the Cessie deed (over-collecting). This practice frequently involves capitalizing fines and imposing unilateral fees, thereby violating Sharia principles. This research rigorously analyzes the juridical validity of such excessive collection practices from the dual perspectives of Substantive Justice and Sharia Economic Law. Employing a normative legal research method with statute, conceptual, comparative, and case approaches, this study examines the stark disparity in religious court decisions and compares regulations across jurisdictions, including Indonesia, Malaysia, Kuwait, and Egypt. The findings reveal that over-collecting fundamentally violates the civil law principle of Nemo Plus Juris Ad Alium Transferre Potest Quam Ipse Habet and the Sharia prohibition of Riba (usury) and Zhulm (oppression). Through the lens of John Rawls’ theory, it breaches the Difference Principle by exacerbating the plight of the debtor as the least advantaged party. Consequently, such actions are legally void. The study recommends a regulatory formulation through the Financial Services Authority (OJK) by establishing a specific